First insight into how stress exposure triggers Vibrio harveyi recipient successful conjugation - Deng, Yiqin; Gao, Si’ao; Xu, Liwen; Cheng, Changhong; Ma, Hongling; Feng, Juan (Frontiers in Marine Science, 2023)
Conjugation is the most common horizontal gene transfer (HGT) process that can be affected by environmental change and promote bacterial virulence and drug resistance. However, it is unknown whether environmental changes can influence the conjugation ability of the marine fish pathogen Vibrio harveyi, thereby affecting its pathogenicity and drug resistance. This study systematically analyzes the effect of environmental stress on the ability of V. harveyi to obtain shuttle plasmids from Escherichia coli during conjugation. The results indicate that V. harveyi cannot receive shuttle plasmid pMMB207 without exposure to stress. However, certain stress exposure (37–46°C, 4%–16% ethanol, 0.14–0.56 mM SDS, 0.04~0.05 M NaOH, and 0.012–0.024 M HCl for 5–60 minutes) in the log phase of V. harveyi before conjugation successfully induces the fertility of the V. harveyi recipient in intergeneric mating with E. coli. In particular, ethanol and heat stress showed strong induction with up to 2.5 × 105 and 5.3 × 103 transconjugants when exposed to 16% ethanol for 10 minutes and 40°C for 60 minutes, respectively. Additionally, appropriate levels of NaOH (0.05 M, 10 minutes), SDS (0.42 mM, 5 minutes), and HCl (0.024 M, 5 minutes) lead to 2.3 × 103, 4.5 × 102, and 1.8 × 102 transconjugants, respectively. These results will help establish homologous recombination gene knockout technology and greatly advance molecular theoretical research on V. harveyi. They will also support the establishment of disease prevention and control strategies based on the interruption of the HGT process by environmental regulation.